THE SCIENTIFICITY IN THE ACCOUNTING DISCIPLINE - Torres Gallardo, Arturo (2012)
At present, the consideration of knowledge as scientific or not, is the result of applying conventional character criteria established by men in a subjective and sometimes arbitrary way. As mentioned by Montes (2006), the canons of science are effective space-time, the criteria at a time or place can be described as scientific, in another time or place can be metaphysical. The aim of this scientific article is to know the elements or components of a science, which have been deducted from the literature reviewed, carefully observing the different definitions of science that every school of thought says. This shows the evolutionary process of science, as a result of the different schools of thought exist, which according to their view, could raise awareness of different ways of understanding the nature, phenomena, reality, etc., precisely because using the method of obtaining scientific knowledge. The bibliographical sources consulted, are related to the Philosophy of Science. The methods are basically based on: historical, analytic-synthetic, deductive, hermeneutic. We found that regardless of the independent school of thought that favors this or that method, all have shown in their definition of science elements or common components along their evolutionary process and we might say it characterizes all science. We have identified three components of all knowledge: the object of study, the method and predictability.